(untitled) (Research, Society and Development, 2022)
Background: The covid-19 pandemic showed how understanding the epidemiology of specific populations is extremely necessary for adequate health care. For this, it is necessary to know the health-disease profile of the military population (which differs from civilians), but free from the biases that the exceptional events of this catastrophe could generate. Aims: The study aims to characterize the temporal trend and the profile of hospitalizations of active-duty military admitted to the Brazilian Army Central Hospital from 1998 January 1st to 2018 December 31st (before Covid-19 pandemic). Methodology: Analytical cross-sectional study with non-nominal secondary data from the records of the Hospital Information System of the Brazilian Army Central Hospital. Simple linear regression (p<0.005) and descriptive statistics were performed. Results: 20,292 hospitalizations were recorded in the period, of which 93.2% were for males (no change in time trend) and 6.2% were for female (with a significant increase in the historical series). Among males, the predominant age bracket was “21 to 30 years old” (44.5%), “brown” race (47.3%), “Corporals and Soldiers” ranks (61.8%) and hospitalized by the group of specialties of “Orthopedics, Traumatology, and Rheumatology” (33.9%). For females, the predominant age bracket was “31 to 40 years old” (51.4%), “white” race (55%), “Non-commissioned officers” ranks (58.9%) and hospitalized by the group of specialties “Gynecology and Obstetrics” (43, 1%). Conclusions: During the studied period, among the active-duty military personnel hospitalized, there was a predominance of males, young, Corporals and Soldiers with musculoskeletal impairment.